The link between self-uncertainty and conspicuous consumption: Tolerance of uncertainty as a moderator - Wang, Xiaoming; Zhu, Hongjin; Zhao, Qinying; Song, Chaoqi; Wang, Xiuxin (Frontiers in Psychology, 2023)
This study, based on self-affirmation theory, aims to investigate the impact of self-uncertainty on individual consumption behavior. Self-uncertainty was categorized into moral, cognitive, and interpersonal self-uncertainty, and different types of self-uncertainty were manipulated through four experiments, including a moral dilemma, a recall paradigm, and a picture quiz task written by E-Prime software to examine the effects of different types of self-uncertainty on conspicuous consumption and their possible boundary conditions. Our results show that moral, cognitive, and interpersonal self-uncertainty contribute to a stronger tendency to engage in conspicuous consumption. Our results also suggest that tolerance of uncertainty moderates the effect of self-uncertainty on conspicuous consumption, meaning that subjects with a high tolerance of uncertainty are less inclined to engage in conspicuous consumption than those with a low tolerance of uncertainty, even if they have high self-uncertainty. This study may provide an explanation for conspicuous consumption behavior, further validating the theory of compensatory consumption. Additionally, the results from this study also provide a reference for understanding people’s decision-making behavior in an uncertain social context and can provide new guidance to control irrational consumption behavior.